Effect of Allelopathic Potential of Corn, Sunflower , Field Capacity and Ascorbic Acid In Growth of Two Wheat cultivars - mohamed fisal (College of Education for Pure Sciences, 2020)
Abstract This study was carried out inside a wired house and included the planting two cultivars of wheat (Sham 6 - IPA 99) in soils containing residues of corn (Zea may) and sunflower (Helianthns annuus) with exposing plants to three levels of field capacity (35, 60, 85%) and spraying plants with three concentrations of ascorbic acid (0, 100, 200) ppm in order to know the effect of these factors on some physiological, biochemical and allelopathic potential of wheat. The experiment has been designed on the basis that it is factorial and over completely Randomized Design (C.R.D) Duncan's multiple range test at 5% level was used to compare between the means and the results showed. The addition of corn residues and sunflower showed a great effect in lowering plant height, relative water content, chlorophyll, number of grains / spike and grains yield with the increasing the concentration of catalase. Exposure of plants to drought (35% field capacity) showed a negative effect on all traits above comparing to field capacity (60, 85%) except for the increase in antioxidant enzymes (Peroxidase, Catalase). Plants submitted under two types of stress (drought + allelopathy) can improve their growth and reduce the negative effect of drought and the inhibitory effect of residues by treating it with ascorbic acid especially in the concentration 200 ppm. More over, sham 6 was significantly superior on IPA 99 in most physiological and biochemical characters, which was reflected in the increasing grains yield. Keywords: allelopathy, Field capacity, Ascorbic acid, wheat.